A Retrospective Observational Study on the Prescribing Patterns, Polypharmacy, ADR of Antiphsychotic Medications and Impact on MHQoL - Rachamsetty Kavya, Senthilraj R (South Eastern European Journal of Public Health, 2025)
Psychiatric disorders are important cause for disability and therapeutic burden in developing countries like India. Various antipsychotic drugs are used to treat mental disorders which are notable to cause side effects and adverse drug reactions (ADR). Due to the limited data available on the prevalence of ADR in psychiatric prescription drugs, this study was conducted to evaluate the prescription patterns, polypharmacy and ADR due to antipsychotic medications. The retrospective observational study was conducted in Govt.Medical College and Govt General Hospital, Ongole, Prakasam, Andhra Pradesh from July 2022-December 2023 on 205 prescriptions. the patient demographic details like age, gender and disease status were noted. Prescriptions were evaluated for ADR, polypharmacy with more than 2-3 drugs of same class. All the participants were divided into 2 groups A, which received counselling and B, which didnot receive any counselling. The participants were evaluated for Mental Health Quality of Life (MHQoL). This retrospective study of 205 participants analyzed gender, age, and psychiatric disorder distribution, revealing that females (57.56%) and the 31-40 age group (43.41%) were predominant. Manic and bipolar disorders were the most common, and diabetes was the leading comorbidity. Polypharmacy, particularly with antipsychotics, antidepressants, and anti-anxiety drugs, was prevalent. The study also found that 90.77% of antipsychotics were prescribed generically, though only 52.64% were on the Essential Drugs List. Counseling significantly improved Mental Health Quality of Life (MHQoL) scores, highlighting its effectiveness in enhancing mental health outcomes compared to those without counseling. The study highlights the need for vigilant monitoring of ADRs, particularly from polypharmacy with antidepressants, which are mostly mild and preventable. It emphasizes ongoing studies and adherence to international guidelines in antipsychotic prescriptions, along with baseline investigations, to optimize patient care and improve health outcomes.